مقاصد سور القرآن عند البقاعي (ت 885 هـ) دراسة نظرية تطبيقية: The Objectives of Qur'anic Chapters According to Al-Baqā’i (D. 885 H): A Theoretical and Applicative Study - Cica Maulina Beni (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This research belongs to the field of Maqāṣid al-Suwar (Objectives of Qur'anic Chapters) and is titled: